Factores de riesgo asociados a sobrepeso y obesidad en niños de nivel primario de una institución educativa pública y una privada de Iquitos, 2024 - Garcia Claudio, Alejandra Joana del Rosario (2025)
Objective: To determine the risk factors associated with overweight and obesity in primary school children from a public and a private educational institution in Iquitos, 2024. Methodology: An observational, analytical, and cross-sectional study that interviewed, measured, and weighed 218 children aged 6 to 11 years from a public and a private educational institution, selected through simple random sampling. Results: A higher prevalence was identified in the obesity group (20.64%) compared to the overweight group (20.18%). According to school type, higher overweight (27.0%) and obesity (30.9%) rates were identified in children from the private school compared to the public school (23.8% and 20%, respectively). Risk factors associated with overweight were: enjoying physical activity or sports (PR: 21.8; CI: 20.7–23.1; p=0.000), (PR: 3.87; CI: 1.53–9.78; p=0.004), and not watching television (PR: 4.38; CI: 1.77–10.85; p=0.001); no risk factors associated with overweight were identified in the public educational institution. Risk factors associated with obesity were: sleeping less than 9 hours (PR: 0.37; CI: 0.15–0.89; p=0.028), not having breakfast before going to school (PR: 0.29; CI: 0.13–0.67; p=0.004), consuming sweets, chocolates, or chips as a snack (PR: 0.40; CI: 0.16–0.99; p=0.048), wanting to change something about their body (PR: 3.79; CI: 1.61–8.90; p=0.002), enjoying physical activity or sports (PR: 21.8; CI: 20.7–23.1; p=0.000), engaging in physical activity after school (PR: 0.02; 95% CI: 10.01–0.10; p=0.000), and not watching television (PR: 2.53; CI: 1.09–5.84; p=0.030). In the private educational institution, a significant increase in obesity was associated with: enjoying physical activity and not watching television; in contrast to the public educational institution, where only body dissatisfaction was associated. Conclusions: The study found a higher prevalence of obesity compared to overweight. Furthermore, children from the private school in Iquitos had higher rates of overweight and obesity than those from the public school. These results were associated with differences in risk and protective factors between the two institutions, including sleep habits, breakfast consumption, physical activity levels, and body image perception